PHARMACOECONOMIC ANALYSIS OF THE USE OF RIBOMUSTIN® IN THERAPY OF THE FIRST LINE OF A MULTIPLE MYELOMA FOR PATIENTS MORE SENIOR 65 YEARS OLD - A. S. Kolbin; I. A. Vilum; Yu. E. Balykina; M. A. Proskurin (Фармакоэкономика, 2015)
Abstract: we have performed the first-ever comparative pharmacoeconomic analysis in a Russian context of bendamustine in the first line of therapy of a multiple myeloma for for patients more senior 65 years old with clinical manifestations of a polineuropathy, which autological transplantation of stem cells isn’t shown. Research was conducted from a position of the state health system by means of mathematical modeling. Markov modeling and the sensitivity analysis were used. For primary patients who aren’t candidates for transplantation the following regimes of treatment were compared of: bendamustine + prednisone; melphalan + prednisone; bortezomibe + dexamethasone. The results show that the use of bendamustine in the first line of therapy of a multiple myeloma for elderly patients with the phenomena of a polyneuropathy is economically expedient from the point of view of a ratio of cost and efficiency.